Sporochartines A–E, A New Family of Natural Products from the Marine Fungus Hypoxylon monticulosum Isolated from a Sphaerocladina Sponge - Leman-Loubière, Charlotte; Le Goff, Géraldine; Debitus, Cécile; Ouazzani, Jamal (Frontiers in Marine Science, 2017)
Four new sporochartines B-E were isolated from the marine fungus Hypoxylon monticulosum CLL-205, isolated from a sponge belonging to the Sphaerocladina order and collected in Tahiti coast. Sporochartine A (1), the first representative of this family was previously isolated from the same fungus. The structures of sporochartines B-E were elucidated using 1D and 2D NMR, HRMS and IR data. Their configurations were established according to ROE correlations and comparison with the absolute configuration of sporochartine A (1) previously obtained from X-ray analysis. Sporochartines A-D (2-4) may be derived from endo Diels-Alderase type catalysis and sporochartine E (5) from an exo Diels-Alderase catalysis. The spatial conformation of sporochartines drastically influences the results of the cytotoxic bioassay against HCT-116, PC-3 and MCF-7 human cancer cell lines.